Evaluation of gut microbiota alterations following orlistat administration in obese mice - Xue, Chang; Wang, Tianying; Chen, Yang; Zhang, He; Wang, Hongjie; Li, Qiang (Frontiers in Endocrinology, 2025)
BackgroundThe gut microbiota plays a pivotal role in various metabolic disorders. Orlistat has shown beneficial effects on weight loss and metabolism, but its direct impact on the gut microbiota has not been extensively reported. Thus, this study aimed to explore the effects of orlistat on the gut microbiota in mice with high-fat diet-induced obesity.MethodsThirty male C57BL/6J mice were randomly divided into a normal control group (fed a standard diet, N), and a model group (fed a 60% fat diet). A body weight exceeding the basal body weight by 130% defined a successfully established obesity model. The model group was further divided into a positive control group (fed a 60% fat diet, F), and an orlistat group (fed a 60% fat diet and treated with orlistat at 30 mg/kg, bid, A), with 10 mice in each group. The parameters assessed included weight loss, fasting plasma glucose (FPG) levels, and intestinal hormones. Gut microbiota diversity was analyzed using high-throughput sequencing.ResultsOrlistat treatment significantly reduced body weight and FPG levels, and increased glucagon-like peptide-1 (GLP-1) and gastric inhibitory polypeptide (GIP) levels in obese mice. High-fat diet-fed mice exhibited increased microbial diversity and richness, which were significantly diminished by orlistat administration. Additionally, orlistat treatment led to a significant decrease in the proportion of Bacteroidetes and an increase in the proportion of Helicobacter and Allobaculum. Notable shifts in the abundances of Bacteroidetes were observed, correlating with changes in several functional metabolic pathways, including “cell motility” and “neurodegenerative diseases.” Co-occurrence network analysis suggested a more complex bacterial network in orlistat-treated mice, alongside a reduction in the density of bacterial correlation networks.ConclusionsOur study demonstrates that orlistat’s beneficial effects on body weight, FPG, GLP-1, and GIP are likely mediated through modifications in the gut microbiota composition.